Цифрова трансформація стратегічного управління в Україні: євроінтеграційний вимір - Ортіна, Ганна Володимирівна; Ortina, Hanna (Запоріжжя : Видавничий дім «Гельветика», 2025)
UA: У статті досліджено процес цифрової трансформації стратегічного управління в Україні в контексті євроінтеграційних прагнень держави. Розкрито особливості впровадження цифрових стратегій, цифрових платформ та аналітичних інструментів, які впливають на ефективність державного управління. Проведено SWOT-аналіз цифрового стратегічного управління в Україні. Розглянуто кейс-стаді реалізації цифрових ініціатив у сфері публічного адміністрування, а також визначено роль таких європейських програм, як "Digital Europe", у підтримці українських реформ. Надано практичні рекомендації щодо зміцнення цифрової спроможності органів влади та їх відповідності стандартам ЄС. /// EN: This article comprehensively examines the process of digital transformation of strategic public administration in Ukraine in the context of its ongoing European integration. As Ukraine moves towards aligning its governance structures with EU standards, digitalization emerges not only as a technical process but also as a strategic imperative aimed at increasing transparency, efficiency, and accessibility of public services. The study outlines the evolution of national digital strategies, focusing on key policy documents, institutional frameworks, and the role of government-led platforms such as “Diia.” Particular attention is paid to the implementation of digital platforms, the automation of administrative procedures, and the integration of analytical and monitoring tools to improve decision-making in public administration. A detailed SWOT analysis is presented to assess the strengths, weaknesses, opportunities, and threats associated with Ukraine’s digital governance landscape. Strengths include the political will to implement digital reforms and the initial success of public service platforms. Weaknesses involve the uneven development of digital infrastructure, regional disparities, and insufficient digital literacy among civil servants. Opportunities are identified in the growing international support from the EU, including the “Digital Europe” program, while key threats include cyber security vulnerabilities and a lack of coordinated digital strategies across government bodies. The article also features case studies that highlight successful digital governance practices at national and regional levels, illustrating how digital tools are being applied in post-crisis recovery, citizen engagement, and transparency mechanisms. These examples demonstrate the potential of digital transformation to improve governance effectiveness and institutional resilience in Ukraine. Based on the analysis, the paper offers practical recommendations for enhancing the digital capacity of public institutions. These include improving interagency coordination, investing in digital infrastructure, ensuring comprehensive cybersecurity frameworks, developing training programs for civil servants, and establishing partnerships with EU digital institutions. Ultimately, the research emphasizes that a successful digital transition in Ukraine requires a holistic and inclusive approach that addresses not only technological, but also institutional, legal, and societal aspects of reform. Digital transformation, when implemented strategically, can become a powerful driver of Ukraine’s sustainable development and its integration into the European administrative space.
Digital transformation of strategic management in Ukraine: the european integration dimension
Keywords: цифрова трансформація; стратегічне управління; євроінтеграція; публічне адміністрування; цифрові платформи; SWOT-аналіз; Digital Europe; інноваційне управління; Digital transformation; strategic management; European integration; public administration; digital platforms; SWOT analysis; innovative governance